2016
DOI: 10.1016/j.drugalcdep.2016.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Medical marijuana legalization and cigarette and marijuana co-use in adolescents and adults

Abstract: Background Medical marijuana legalization is associated with a higher prevalence of marijuana use which may affect cigarette use and nicotine dependence in co-users. In the present study, we examined relationships between statewide legalization of medical marijuana and prevalence of cigarette and marijuana co-use and nicotine dependence in co-using adolescents and adults. Methods Data were analyzed from the 2013 National Survey on Drug Use and Health. We compared cigarette and marijuana co-use in the past 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 51 publications
0
52
0
1
Order By: Relevance
“…E-cigarette and hookah use is more prevalent than combustible cigarette smoking among adolescents, yet e-cigarettes and hookah are far less regulated. 10,37 Federal regulations do not currently restrict youthtargeted advertising and promotion or sales of youth-friendly flavors of 31,39 With the data from the current study, we raise questions regarding the impact of less restrictive policies on the use and co-use of newer tobacco products and marijuana in the adolescent population. These data are used to support strict policies to prevent tobacco product and marijuana product sales to minors.…”
Section: Discussionmentioning
confidence: 88%
“…E-cigarette and hookah use is more prevalent than combustible cigarette smoking among adolescents, yet e-cigarettes and hookah are far less regulated. 10,37 Federal regulations do not currently restrict youthtargeted advertising and promotion or sales of youth-friendly flavors of 31,39 With the data from the current study, we raise questions regarding the impact of less restrictive policies on the use and co-use of newer tobacco products and marijuana in the adolescent population. These data are used to support strict policies to prevent tobacco product and marijuana product sales to minors.…”
Section: Discussionmentioning
confidence: 88%
“…for reviews) that may lead persons who have problematic cannabis use (eg, CUDs), or who report cannabis use, to have more difficulty quitting cigarette smoking. Persons who co-use cigarettes and cannabis report smoking more cigarettes per day49 50 and symptoms of nicotine dependence50–52; both of which are associated with increased difficulty quitting smoking (eg, refs 53–56…”
Section: Discussionmentioning
confidence: 99%
“…Also, as the legal status of cannabis and the prevalence of use changes, considerations should be given to how these policies impact tobacco-cannabis co-use. A recent study found that in states with legalized medical marijuana, co-use was associated with greater odds of nicotine dependence compared to tobacco-only users (Wang et al, 2016). Even with many unanswered questions regarding co-use, the literature to date raises treatment-related concerns for interventions that are developed for cannabis alone, but are recruiting a co-using sample, and in the development of interventions for both substances.…”
Section: Discussionmentioning
confidence: 99%